Temperature effects on electric charge transport processes and electron emission in PBS–clay nanocomposites submitted to electron bombardment - Taktak, Sirine; Fakhfakh, Slim; Rondot, Sébastien; Tara, Ahmed; Jbara, Omar (Journal of Physics D: Applied Physics, 2023)
The effects of isothermal conditions on the charge transport processes and electron emission properties of polybutylene succinate (PBS) nanocomposites with different nanoclay content are investigated. The temperature range used (20 °C–80 °C) is close to the working conditions of materials used in many applications (insulation, sensors). These effects are highlighted using an appropriate device placed in a scanning electron microscope, allowing measurement of induced current in an electron-irradiated specimen. The experimental results show that the rise in temperature involves a decrease in the charging ability and an increase in the conductivity of PBS nanocomposites. The mobility of charge carriers and its thermal dependency deduced during the discharge step were found to be lower for the nanocomposites. A qualitative analysis, expressed to understand these observations, is based on the determination of the electron trap energy distribution (i.e. density of occupied states). Secondary electron emission yield decreased with increasing temperature. The results help us envision a new class of insulators with improved electrical performance. The operating thermal stress, combined with the absence of trapped charges, allows a reduction of electrical and thermal aging and consequently ensures the long-term reliability of the insulators (for instance under High Voltage).